Web-based Indigenous Village P Web-Based Traditional Village Population Administration System in Jimbaran Village, South Kuta, Badung - Mahendra Sastra Adhi Wiguna Gede; Nur Fadhillah Muhamad; Trisanjaya Purba Ghaniel; Aldo Dzar Al-Ghifari; Yudisthira Arimbawa Saputra I Gusti Ngurah Agung; Dionicius Hadarian; I Putu Amara Setia Putra; Patriot Akbar; Taufikur Rohman; Pramuditya Adha Ra'afarudin; I Wayan Supardi; Ni Nyoman Rupiasih; Nyoman Wendri (BULETIN FISIKA, 2025)
The population administration in Jimbaran Traditional Village faces challenges of inefficiency and data inconsistency due to manual processes, especially in managing unique data structures such as NPK (Family Registration Number), NIKA (Traditional Community Registration Number), and Dadia. To address these issues, a web-based administrative information system was developed using the Prototyping method with the Laravel framework, MySQL database, and an interface built using Tailwind CSS and Alpine.js. The resulting system features key functionalities such as centralized master data management, dynamic input forms with automatic NPK and NIKA numbering, management of Traditional Family Card membership, and an integrated correspondence service module. The implementation results demonstrate that this application successfully serves as a functional solution for centralizing data, accelerating administrative services, and enhancing the accuracy of population data in accordance with the specific needs of the traditional village.